Perspektif Ahmad Musthofa Al Maraghi tentang Inklusi Sosial Kaum Marginal: (Analisis Tematik dalam Kitab Tafsir Al Maraghi) - Samani Samani; Khoirul Huda; Maria Ulfah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to describe Al-Maraghi's interpretation of social inclusion and its implementation in the development of an inclusive Indonesian society. This study is qualitative, drawing on the text of Tafsir Al-Maraghi in relation to the concept of social inclusion. Data collection techniques were based on relevant literature, specifically Al-Maraghi's Tafsir from predetermined sources, and using theme analysis. The results of the study revealed several verses of the Quran related to social inclusion issues, including: Surah Al-Nisa' 4:58; Surah Al-Ma'un 107:1-3; Surah Al-Hujurat 49:13; Surah Al-Taubah 9:60; Surah Al-'Alaq 96:1-5; and Surah Al-Kafirun 109:6. In the several verses above, the application of the value of social inclusion in the development of society in Indonesia, with the importance of social justice, equality, attention to marginalized groups, according to Al-Maraghi's view in his interpretation, makes a significant contribution, and can be used as study material for policy makers, social activists and the wider community to move towards more inclusive and fair thinking in realizing a peaceful life for Muslims in the present and future. Keywords: Social Integration, Marginalized, Maraghi